Dielectric and magnetic loss coupling type multi-frequency high-absorption composite wave-absorbing material and preparation method thereof
Through the composite and process optimization of FeCoNiCrMn-based high-entropy alloy and barium titanate, the problems of insufficient absorption performance and environmental instability of existing wave absorbing materials in multi-bands are solved, and efficient and stable multi-band electromagnetic wave absorption effect is achieved.
Patent Information
- Application Number
- CN202411595571.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-01-14
AI Technical Summary
Existing absorbing materials have shortcomings in meeting multi-band, efficient absorbing and environmental stability. Especially traditional materials are prone to corrosion and high-temperature oxidation, making it difficult to show excellent absorbing performance in wide bands.
FeCoNiCrMn-based high-entropy alloy is combined with barium titanate, and the magnetic loss capacity is provided through FeCoNiCrMn-based high-entropy alloy and barium titanate provides dielectric loss capacity, realizing dielectric and magnetic loss coupling, and combining suspension smelting and vacuum atomization process preparation Composite absorbing materials, reinforced materials with corrosion resistance and high temperature oxidation resistance.
It achieves the improvement of efficient wave absorption performance in multi-bands, while ensuring the environmental stability of the material, has excellent corrosion resistance and high-temperature oxidation resistance, and is suitable for multi-band electromagnetic wave absorption.
Smart Images

Figure CN119317089A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of wave absorbing materials, and in particular relates to a dielectric and magnetic loss coupling type multi-frequency high absorption composite wave absorbing material and a preparation method thereof. Background Art
[0002] With the rapid development of modern electronic technology and wireless communication technology, the problem of electromagnetic wave pollution is becoming increasingly serious, and the demand for electromagnetic wave absorbing materials is also increasing. Electromagnetic wave absorbing materials must not only have good electromagnetic wave absorption performance, but also be lightweight, efficient, wide-band and have excellent environmental stability. Although traditional absorbing materials such as ferrites, carbon materials and conductive polymers have excellent performance in some aspects, they still have limitations in meeting the comprehensive requirements of multi-band, high-efficiency absorption and environmental stability (easy to corrode and oxidize at high temperature).
[0003] As an emerging material system, high entropy alloy is composed of five or more main elements and has excellent mechanical properties, corrosion resistance and thermal stability. Since it usually contains magnetic elements such as Fe, Co, and Ni, it exhibits excellent magnetic properties such as high saturation magnetization, low coercive force and high Curie temperature, and also shows good potential in electromagnetic wave absorption. However, the wave absorption ability of high entropy alloys alone is difficult to meet the needs of multi-band efficient and stable wave absorption. If barium titanate with excellent dielectric loss capacity is compounded with high entropy alloys, it is expected to achieve the goals of multi-band, efficient wave absorption and environmental stability.
[0004] Therefore, the present invention proposes a dielectric and magnetic loss coupled multi-frequency high-absorption composite absorbing material and a preparation method thereof. Through reasonable material design and process optimization, a composite material with excellent absorbing performance in a wide frequency band is obtained, which can effectively solve the problems of insufficient multi-band absorbing performance and environmental instability in the prior art. Summary of the invention
[0005] The purpose of the present invention is to overcome the deficiencies in the above-mentioned prior art and provide a dielectric and magnetic loss coupled multi-frequency high-absorption composite absorbing material. The composite absorbing material is compounded by FeCoNiCrMn high entropy alloy and barium titanate, and the magnetic loss capacity is provided by the FeCoNiCrMn high entropy alloy and the dielectric loss capacity is provided by the barium titanate, so as to achieve the synergistic effect of multiple loss mechanisms. At the same time, the FeCoNiCrMn high entropy alloy also has corrosion resistance and high temperature oxidation resistance, which can make the composite absorbing material environmentally stable, and solve the problems of insufficient multi-band absorbing performance and environmental instability in the prior art.
[0006] To achieve the above object, the technical solution adopted by the present invention is: a dielectric and magnetic loss coupling multi-frequency high absorption composite absorbing material, characterized in that the chemical formula of the composite absorbing material is (FeCoNiCr a Mn) x ·(BaTiO3) y , the value range of a is 0.1~1, and the ratio of y to x is not greater than 1.
[0007] The dielectric and magnetic loss coupling multi-frequency high absorption composite absorbing material is characterized in that the chemical formula of the composite absorbing material is (FeCoNiCr 0.8 Mn)1·(BaTiO3) 0.2 .
[0008] The present invention controls the content of each element to obtain a composite wave absorbing material with optimal wave absorbing performance.
[0009] In addition, the present invention also discloses a method for preparing the above-mentioned dielectric and magnetic loss coupling type multi-frequency high absorption composite absorbing material, which is characterized in that the preparation method comprises the following steps:
[0010] Step 1: Mix metal iron, metal cobalt, metal nickel, metal chromium and metal manganese and perform suspension smelting multiple times to prepare alloy ingots, then perform vacuum gas atomization, and obtain high entropy alloy spherical powder after sieving;
[0011] Step 2: subjecting the high entropy alloy spherical powder obtained in step 1 to a first ball milling under an argon atmosphere to obtain a lamellar high entropy alloy; a process control agent is added during the first ball milling;
[0012] Step 3, naturally cooling the flaked high entropy alloy obtained in step 2 and then drying it to obtain a dry flaked high entropy alloy;
[0013] Step 4: Mix the dried flaky high entropy alloy obtained in step 3 with barium titanate powder, and then perform a second ball milling in an argon atmosphere. After natural cooling, a product having a chemical formula of (FeCoNiCr a Mn) x ·(BaTiO3) y The composite absorbing material; the second ball mill adopts a dry grinding process.
[0014] The present invention adopts a method of combining vacuum gas atomization with two-step ball milling to prepare a composite absorbing material. First, a spherical high entropy alloy powder is prepared by a suspension melting furnace and a vacuum gas atomization process, and then a first ball mill is used to implement a flaking treatment of the high entropy alloy powder. The flaking treatment increases the surface polarization effect of the high entropy alloy, and effectively improves the impedance matching of the performance required as the absorbing material. By adding a process control agent during the first ball milling, the force between the spherical high entropy alloy powder and the grinding ball can be weakened, the internal stress of the spherical high entropy alloy powder can be reduced, and then the soft magnetic properties of the spherical high entropy alloy powder can be improved, including reducing the coercive force and increasing the saturation magnetization intensity. Furthermore, the high entropy alloy powder after the flaking treatment is combined with barium titanate for a second ball milling. The ball milling process is a dry milling process without adding any process control agent, so that atomic diffusion can be carried out between the high entropy alloy powder and the barium titanate powder to achieve efficient organic coupling. Based on a suspended melting furnace, vacuum gas atomization and a two-step ball milling method, a barium titanate-doped high-entropy alloy composite absorbing material with both magnetic loss and dielectric loss mechanisms can be prepared, which has the characteristics of multi-frequency and high-efficiency absorption.
[0015] The present invention adopts metal iron, metal cobalt, metal nickel, metal chromium and metal manganese as raw materials to prepare high entropy alloy, and the high entropy alloy has excellent corrosion resistance and high temperature oxidation resistance, so that the composite absorbing material has excellent performance stability in service environments such as ocean and high temperature.
[0016] The above-mentioned method for preparing a dielectric and magnetic loss coupling type multi-frequency high-absorption composite absorbing material is characterized in that the mass purity of the metal iron, metal cobalt, metal nickel, metal chromium and metal manganese in step one is greater than 99.7%.
[0017] The above-mentioned method for preparing a dielectric and magnetic loss coupling type multi-frequency high absorption composite absorbing material is characterized in that the vacuum degree of the suspension melting in step 1 is not greater than 1×10 -3 After each suspension smelting, the alloy ingot is turned over, and the number of suspension smelting is not less than 5 times; the vacuum degree of the vacuum gas atomization is not greater than 1×10 -3 The temperature of the vacuum air atomization is 1200° C. to 1600° C., the heating power of the vacuum air atomization is 10 kW to 25 kW, and the heating time of the vacuum air atomization is 60 min to 100 min.
[0018] The present invention controls the parameters in the suspension smelting and vacuum gas atomization process to ensure the uniformity of the chemical composition of the high entropy alloy spherical powder and to improve the powdering rate of the powder with the required particle size, thereby improving the utilization rate of the raw materials and facilitating the increase in the output of the composite absorbing material.
[0019] The above-mentioned method for preparing a dielectric and magnetic loss coupled multi-frequency high-absorption composite absorbing material is characterized in that the sieving time in step one is 10 minutes to 45 minutes, the particle size of the high-entropy alloy spherical powder is not greater than 53 μm, and the mass of the high-entropy alloy spherical powder accounts for 40% to 60% of the total mass of the vacuum atomization product.
[0020] The present invention screens the vacuum gas atomization product so that the particle size of the obtained high entropy alloy spherical powder is no more than 53 μm, and the particle size is more conducive to subsequent ball milling.
[0021] The above-mentioned method for preparing a dielectric and magnetic loss coupled multi-frequency high-absorption composite absorbing material is characterized in that the first ball milling process in step 2 is: the high entropy alloy spherical powder and the process control agent are loaded into a stainless steel ball mill for vacuum pump evacuation and argon gas washing, and after sealing, the ball mill is loaded into a high-energy ball mill for 12h to 24h ball milling, and the high-energy ball mill is stopped for 5min to 8min after each 30min to 60min of ball milling; the first ball milling speed is 300r / min to 600r / min, the mass ratio of stainless steel grinding balls to high entropy alloy spherical powder in the stainless steel ball mill is 5 to 20:1, and the diameter size of the stainless steel grinding balls includes one or more of 10mm, 8mm and 6mm.
[0022] The above-mentioned method for preparing a dielectric and magnetic loss coupled multi-frequency high-absorption composite absorbing material is characterized in that the process control agent in step 2 is one of anhydrous ethanol, stearic acid, acetone, and deionized water, and the added amount of the process control agent is 10mL to 50mL.
[0023] The present invention adjusts the sealing operation process of the ball mill to ensure that the high entropy alloy spherical powder in the ball mill is always in an inert atmosphere during high-energy ball milling; and controls the mass ratio of stainless steel grinding balls to the high entropy alloy spherical powder, the size of the stainless steel grinding balls, the ball milling process, and the type and added content of the process control agent, so that the high entropy alloy powder can be fully flaked to achieve an optimal surface polarization effect.
[0024] The above-mentioned method for preparing a dielectric and magnetic loss coupled multi-frequency high-absorption composite absorbing material is characterized in that the drying in step three is vacuum drying, the drying temperature is 40°C to 80°C, and the drying time is 8h to 30h.
[0025] The invention adopts vacuum drying to avoid oxidation of powder, and controls drying temperature and time to completely volatilize the residual process control agent in the ball mill.
[0026] The above-mentioned method for preparing a dielectric and magnetic loss coupled multi-frequency high-absorption composite absorbing material is characterized in that the second ball milling in step four uses a high-energy ball mill, the rotation speed of the second ball milling is 300r / min~600r / min, and the time of the second ball milling is 20min~60min.
[0027] The present invention adopts a high-energy ball mill for ball milling. Compared with an ordinary ball mill, the high-energy ball mill adopts a more efficient planetary ball milling technology. Through the centrifugal force and friction force generated by the sample and the grinding medium in the ball mill barrel during high-speed rotation, finer grinding of the sample can be achieved.
[0028] Compared with the prior art, the present invention has the following advantages:
[0029] 1. The present invention composites FeCoNiCrMn high entropy alloy with barium titanate, utilizes the magnetic loss capability provided by FeCoNiCrMn high entropy alloy and the dielectric loss capability provided by barium titanate, realizes the synergistic effect of dielectric mechanism and magnetic loss mechanism, and can effectively improve the attenuation coefficient of the absorbing material to improve the absorbing performance of the composite absorbing material.
[0030] 2. The present invention adopts FeMnCoNiCr high entropy alloy. Since the high entropy alloy contains magnetic elements such as Fe, Co, and Ni, it can show excellent magnetic properties such as high saturation magnetization, low coercive force, and high Curie temperature, and also shows good potential in electromagnetic wave absorption. At the same time, due to the cocktail effect unique to high entropy alloys, a variety of randomly mixed metal elements work synergistically, and the addition of Cr elements can make the corrosion resistance formed by the alloy system better than the corrosion resistance of any single element itself, which can effectively improve the corrosion resistance and high-temperature oxidation resistance of the composite absorbing material, so that the composite absorbing material can achieve the excellent performance of multi-frequency and high-efficiency absorption while taking into account the environmental service stability.
[0031] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a microscopic image of the high entropy alloy spherical powder prepared in Example 1 of the present invention.
[0033] Figure 2 This is a microscopic image of the composite absorbing material prepared in Example 1 of the present invention.
[0034] Figure 3 This is a reflection loss test chart of the high entropy alloy spherical powder prepared in Example 1 of the present invention.
[0035] Figure 4This is a reflection loss test chart of the composite absorbing material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0036] Example 1
[0037] The chemical formula of the composite absorbing material of this embodiment is (FeCoNiCr 0.8 Mn)1·(BaTiO3) 0.2 .
[0038] The preparation method of this embodiment comprises the following steps:
[0039] Step 1: Mix metal iron, metal cobalt, metal nickel, metal chromium and metal manganese according to FeCoNiCr 0.8 The materials were weighed according to the atomic percentage of Mn, mixed and then subjected to suspension smelting for 5 times to prepare an alloy ingot, which was then sieved for 30 minutes using a 270-mesh screen after vacuum gas atomization to obtain a high-entropy alloy spherical powder with a particle size of no more than 53 μm; the mass purity of the metal iron, metal cobalt, metal nickel, metal chromium and metal manganese was greater than 99.7%, and the vacuum degree of the suspension smelting was 1×10 -3 After each suspension smelting, the alloy ingot is turned over, and the vacuum degree of the vacuum gas atomization is 1×10 -3 , the temperature of the vacuum air atomization is 1500° C., the heating power of the vacuum air atomization is 25 kW, and the heating time of the vacuum air atomization is 80 min;
[0040] Step 2: 30 g of the high entropy alloy spherical powder obtained in step 1 and 20 mL of anhydrous ethanol are placed in a stainless steel ball mill with 500 g of stainless steel grinding balls, and vacuum pumped twice and purged twice with argon gas. Then, the sealed stainless steel ball mill filled with argon is placed in a high-energy ball mill for 12 hours of ball milling at a speed of 480 r / min, and the high-energy ball mill is stopped for 5 minutes after each 30 minutes of ball milling to obtain a lamellar high entropy alloy; the diameters of the stainless steel grinding balls are 10 mm and 6 mm, and the mass ratio of 10 mm stainless steel grinding balls to 6 mm stainless steel grinding balls is 5:1;
[0041] Step 3: After the lamellar high entropy alloy obtained in step 2 is naturally cooled, it is placed in a vacuum drying oven and dried at 60° C. for 12 hours to obtain a dry lamellar high entropy alloy;
[0042] Step 4: The dried flaky high entropy alloy obtained in step 3 and the barium titanate powder are mixed in a mass ratio of 1:0.2, placed in a ball mill containing stainless steel grinding balls and sealed and filled with argon, and then the sealed ball mill is placed in a high-energy ball mill for 30 minutes at a speed of 480 r / min. After natural cooling, a chemical formula of (FeCoNiCr 0.8Mn)1·(BaTiO3) 0.2 Composite absorbing material.
[0043] The anhydrous ethanol in this embodiment can also be replaced by one of stearic acid, acetone and deionized water other than anhydrous ethanol.
[0044] The microstructure of the high entropy alloy spherical powder prepared in step 1 of this embodiment is analyzed. Figure 1 As shown, the particle size of the high entropy alloy spherical powder is no more than 53 μm and has good sphericity; after testing, the mass of the high entropy alloy spherical powder with a particle size no more than 53 μm accounts for 40% of the total mass of the vacuum gas atomization product.
[0045] The composite absorbing material prepared in this embodiment is subjected to microstructural analysis. Figure 2 As shown, the composite absorbing material has a sheet-like morphology with a certain thickness and a relatively large aspect ratio.
[0046] The reflection loss test of the high entropy alloy spherical powder and the composite absorbing material prepared in this embodiment was carried out under different simulated thicknesses, such as Figure 3 and Figure 4 As shown, compared with the high entropy alloy spherical powder, the reflection loss value of the composite absorbing material is significantly reduced, and the maximum absorption capacity is achieved at a thickness of 1.4 mm. The reflection loss value is -37.2 dB, the effective absorbing bandwidth is less than -10 dB, and is 3.3 GHz. It also has strong absorption in the S (2 GHz to 4 GHz), C (4 GHz to 8 GHz), X (8 GHz to 12 GHz), and Ku (12 GHz to 18 GHz) bands. This indicates that the absorbing performance can be effectively improved by flaking the high entropy alloy spherical powder and compounding it with barium titanate.
[0047] The corrosion current density of the composite absorbing material in a 3.5% NaCl solution is about 1.5×10 -5 A / cm 2 The corrosion potential is about -60.9mV. The high temperature oxidation resistance of the composite absorbing material is tested by thermogravimetric analyzer, and its initial oxidation temperature is 810℃.
[0048] In summary, the composite absorbing material prepared in this embodiment has the characteristics of good absorbing performance, corrosion resistance and high-temperature oxidation resistance, and the powder formation rate of the high-entropy alloy spherical powder in this embodiment is relatively high.
[0049] Example 2
[0050] The chemical formula of the composite absorbing material of this embodiment is (FeCoNiCr 0.8 Mn)1·(BaTiO3) 0.3 .
[0051] The preparation method of this embodiment comprises the following steps:
[0052] Step 1: Mix metal iron, metal cobalt, metal nickel, metal chromium and metal manganese according to FeCoNiCr 0.8 The materials were weighed according to the atomic percentage of Mn, mixed and then subjected to suspension smelting for 5 times to prepare an alloy ingot, and then vacuum gas atomization was performed and sieved for 10 minutes using a 270-mesh screen to obtain a high-entropy alloy spherical powder with a particle size of no more than 53 μm; the mass purity of the metal iron, metal cobalt, metal nickel, metal chromium, and metal manganese was greater than 99.7%, and the vacuum degree of the suspension smelting was 1×10 -3 After each suspension smelting, the alloy ingot is turned over, and the vacuum degree of the vacuum gas atomization is 1×10 -3 , the temperature of the vacuum air atomization is 1500° C., the heating power of the vacuum air atomization is 20 kW, and the heating time of the vacuum air atomization is 100 min;
[0053] Step 2: Put 25g of the high entropy alloy spherical powder obtained in step 1 and 50mL of anhydrous ethanol into a stainless steel ball mill with 500g of stainless steel grinding balls, perform vacuum pump evacuation twice and argon gas washing twice, then put the sealed stainless steel ball mill filled with argon into a high-energy ball mill for 12h of ball milling at a speed of 600r / min, and the high-energy ball mill is stopped for 8min after each 60min of ball milling to obtain a lamellar high entropy alloy; the diameters of the stainless steel grinding balls are 10mm and 6mm, and the mass ratio of 10mm stainless steel grinding balls to 6mm stainless steel grinding balls is 5:1;
[0054] Step 3: After the lamellar high entropy alloy obtained in step 2 is naturally cooled, it is placed in a vacuum drying oven and dried at 40° C. for 20 hours to obtain a dry lamellar high entropy alloy;
[0055] Step 4: The dried flaky high entropy alloy obtained in step 3 and the barium titanate powder are mixed in a mass ratio of 1:0.3, placed in a ball mill containing stainless steel grinding balls and sealed and filled with argon, and then the sealed ball mill is placed in a high-energy ball mill for 20 minutes at a speed of 600 r / min. After natural cooling, a chemical formula of (FeCoNiCr 0.8 Mn)1·(BaTiO3) 0.3 Composite absorbing material.
[0056] After testing, the mass of the high entropy alloy spherical powder with a particle size of no more than 53 μm obtained in step 1 accounts for 45% of the total mass of the vacuum gas atomization product; the minimum reflection loss of the composite absorbing material with a thickness of 1.4 mm prepared in this embodiment is -45.2 dB, and the effective absorbing bandwidth is about 2.7 GHz; the corrosion current density of the composite absorbing material prepared in this embodiment in a NaCl solution with a mass concentration of 3.5% is about 3.2×10 -5 A / cm 2 The corrosion potential is about -75.2mV. The high temperature oxidation resistance of the composite absorbing material is tested by thermogravimetric analyzer, and its initial oxidation temperature is 795℃.
[0057] In summary, the composite absorbing material prepared in this embodiment has the characteristics of good absorbing performance, corrosion resistance and high-temperature oxidation resistance, and the powder formation rate of the high-entropy alloy spherical powder in this embodiment is relatively high.
[0058] Example 3
[0059] The chemical formula of the composite absorbing material of this embodiment is (FeCoNiCr 0.6 Mn)1·(BaTiO3) 0.2 .
[0060] The preparation method of this embodiment comprises the following steps:
[0061] Step 1: Mix metal iron, metal cobalt, metal nickel, metal chromium and metal manganese according to FeCoNiCr 0.6 The materials were weighed according to the atomic percentage of Mn, mixed and then subjected to suspension smelting for 5 times to prepare an alloy ingot, and then vacuum gas atomization was performed and sieved for 40 minutes using a 270-mesh screen to obtain a high-entropy alloy spherical powder with a particle size of no more than 53 μm; the mass purity of the metal iron, metal cobalt, metal nickel, metal chromium, and metal manganese was greater than 99.7%, and the vacuum degree of the suspension smelting was 1×10 -3 After each suspension smelting, the alloy ingot is turned over, and the vacuum degree of the vacuum gas atomization is 1×10 -3 , the temperature of the vacuum air atomization is 1450°C, the heating power of the vacuum air atomization is 15kW, and the heating time of the vacuum air atomization is 80min;
[0062] Step 2: 50 g of the high entropy alloy spherical powder obtained in step 1 and 10 mL of anhydrous ethanol are placed in a stainless steel ball mill with 500 g of stainless steel grinding balls, and vacuum pumped twice and purged twice with argon gas. Then, the sealed stainless steel ball mill filled with argon is placed in a high-energy ball mill for 24 hours of ball milling at a speed of 350 r / min, and the high-energy ball mill is stopped for 5 minutes after each 30 minutes of ball milling to obtain a lamellar high entropy alloy; the diameters of the stainless steel grinding balls are 10 mm and 8 mm, and the mass ratio of 10 mm stainless steel grinding balls to 8 mm stainless steel grinding balls is 4:1;
[0063] Step 3: After the lamellar high entropy alloy obtained in step 2 is naturally cooled, it is placed in a vacuum drying oven and dried at 80° C. for 8 hours to obtain a dry lamellar high entropy alloy;
[0064] Step 4: The dried flaky high entropy alloy obtained in step 3 and the barium titanate powder are mixed in a mass ratio of 1:0.2, placed in a ball mill containing stainless steel grinding balls and sealed and filled with argon, and then the sealed ball mill is placed in a high-energy ball mill for 50 minutes at a speed of 350 r / min. After natural cooling, a chemical formula of (FeCoNiCr 0.6 Mn)1·(BaTiO3) 0.2 The composite absorbing material adopts a dry grinding process.
[0065] After testing, the mass of the high entropy alloy spherical powder with a particle size of no more than 53 μm obtained in step 1 accounts for 48% of the total mass of the vacuum gas atomization product; the minimum reflection loss of the composite absorbing material with a thickness of 2.2 mm prepared in this embodiment is -22.7 dB, and the effective absorbing bandwidth is about 1.9 GHz; the corrosion current density of the composite absorbing material prepared in this embodiment in a NaCl solution with a mass concentration of 3.5% is about 6.1×10 -5 A / cm 2 The corrosion potential is about -82.0mV. The high temperature oxidation resistance of the composite absorbing material is tested by thermogravimetric analyzer, and its initial oxidation temperature is 770℃.
[0066] In summary, the composite absorbing material prepared in this embodiment has the characteristics of good absorbing performance, corrosion resistance and high-temperature oxidation resistance, and the powder formation rate of the high-entropy alloy spherical powder in this embodiment is relatively high.
[0067] Example 4
[0068] The chemical formula of the composite absorbing material of this embodiment is (FeCoNiCrMn)1·(BaTiO3) 0.5 .
[0069] The preparation method of this embodiment comprises the following steps:
[0070] Step 1: weigh metal iron, metal cobalt, metal nickel, metal chromium, and metal manganese according to the atomic percentage of FeCoNiCrMn, mix them, and then perform suspension smelting 5 times to prepare an alloy ingot, and then perform vacuum gas atomization and sieve with a 270-mesh screen for 30 minutes to obtain a high-entropy alloy spherical powder with a particle size not greater than 53 μm; the mass purity of the metal iron, metal cobalt, metal nickel, metal chromium, and metal manganese is greater than 99.7%, and the vacuum degree of the suspension smelting is 1×10 -3 After each suspension smelting, the alloy ingot is turned over, and the vacuum degree of the vacuum gas atomization is 1×10 -3 , the temperature of the vacuum air atomization is 1600° C., the heating power of the vacuum air atomization is 25 kW, and the heating time of the vacuum air atomization is 60 min;
[0071] Step 2: 70 g of the high entropy alloy spherical powder obtained in step 1 and 40 mL of anhydrous ethanol are placed in a stainless steel ball mill with 500 g of stainless steel grinding balls, and vacuum pumped twice and purged twice with argon gas. Then, the sealed stainless steel ball mill filled with argon is placed in a high-energy ball mill for 18 hours of ball milling at a speed of 300 r / min, and the high-energy ball mill is stopped for 7 minutes after each 40 minutes of ball milling to obtain a lamellar high entropy alloy; the diameters of the stainless steel grinding balls are 10 mm and 8 mm, and the mass ratio of 10 mm stainless steel grinding balls to 8 mm stainless steel grinding balls is 4:1;
[0072] Step 3: After the lamellar high entropy alloy obtained in step 2 is naturally cooled, it is placed in a vacuum drying oven and dried at 50° C. for 30 hours to obtain a dry lamellar high entropy alloy;
[0073] Step 4: The dried flaky high entropy alloy obtained in step 3 and the barium titanate powder are stirred and mixed in a mass ratio of 1:0.5, placed in a ball mill containing stainless steel grinding balls and sealed and filled with argon gas, and then the sealed ball mill is placed in a high-energy ball mill for 40 minutes at a speed of 300 r / min. After natural cooling, a chemical formula of (FeCoNiCrMn)1·(BaTiO3) is obtained. 0.5 Composite absorbing material.
[0074] After testing, the mass of the high entropy alloy spherical powder with a particle size of no more than 53 μm obtained in step 1 accounts for 60% of the total mass of the vacuum gas atomization product; the minimum reflection loss of the composite absorbing material with a thickness of 1.5 mm prepared in this embodiment is -41.0 dB, and the effective absorbing bandwidth is about 2.8 GHz; the corrosion current density of the composite absorbing material prepared in this embodiment in a NaCl solution with a mass concentration of 3.5% is about 0.6×10 -5The corrosion potential is about -46.2mV. The high-temperature oxidation resistance of the composite absorbing material is tested by a thermogravimetric analyzer, and its initial oxidation temperature is 850℃.
[0075] In summary, the composite absorbing material prepared in this embodiment has the characteristics of good absorbing performance, corrosion resistance and high-temperature oxidation resistance, and the powder formation rate of the high-entropy alloy spherical powder in this embodiment is relatively high.
[0076] Example 5
[0077] The chemical formula of the composite absorbing material of this embodiment is (FeCoNiCr 0.4 Mn)1v(BaTiO3) 0.3 .
[0078] The preparation method of this embodiment comprises the following steps:
[0079] Step 1: Mix metal iron, metal cobalt, metal nickel, metal chromium and metal manganese according to FeCoNiCr 0.4 The materials were weighed according to the atomic percentage of Mn, mixed and then subjected to suspension smelting for 5 times to prepare an alloy ingot, and then vacuum gas atomization was performed and sieved for 45 minutes using a 270-mesh screen to obtain a high-entropy alloy spherical powder with a particle size of no more than 53 μm; the mass purity of the metal iron, metal cobalt, metal nickel, metal chromium, and metal manganese was greater than 99.7%, and the vacuum degree of the suspension smelting was 1×10 -3 After each suspension smelting, the alloy ingot is turned over, and the vacuum degree of the vacuum gas atomization is 1×10 -3 , the temperature of the vacuum air atomization is 1200° C., the heating power of the vacuum air atomization is 10 kW, and the heating time of the vacuum air atomization is 100 min;
[0080] Step 2: Put 100g of the high entropy alloy spherical powder obtained in step 1 and 20mL of anhydrous ethanol into a stainless steel ball mill with 500g of stainless steel grinding balls, perform vacuum pump evacuation twice and argon gas washing twice, then put the sealed stainless steel ball mill filled with argon into a high-energy ball mill for 20h of ball milling at a speed of 350r / min, and the high-energy ball mill is stopped for 5min after each 30min of ball milling to obtain a lamellar high entropy alloy; the diameters of the stainless steel grinding balls are 10mm and 8mm, and the mass ratio of 10mm stainless steel grinding balls to 8mm stainless steel grinding balls is 4:1;
[0081] Step 3: After the lamellar high entropy alloy obtained in step 2 is naturally cooled, it is placed in a vacuum drying oven and dried at 50° C. for 12 hours to obtain a dry lamellar high entropy alloy;
[0082] Step 4: The dried flaky high entropy alloy obtained in step 3 and the barium titanate powder are mixed in a mass ratio of 1:0.3, placed in a ball mill containing stainless steel grinding balls and sealed and filled with argon, and then the sealed ball mill is placed in a high-energy ball mill for 60 minutes at a speed of 350 r / min. After natural cooling, a chemical formula of (FeCoNiCr 0.4 Mn)1·(BaTiO3) 0.3 Composite absorbing material.
[0083] After testing, the mass of the high-entropy alloy spherical powder with a particle size of no more than 53 μm obtained in step 1 accounts for 55% of the total mass of the vacuum gas atomization product; the minimum reflection loss of the composite absorbing material with a thickness of 2.5 mm obtained in this embodiment is -30.9 dB, and the effective absorbing bandwidth is about 1.7 GHz; the corrosion current density of the composite absorbing material obtained in this embodiment in a NaCl solution with a mass concentration of 3.5% is about 8.2×10 -5 The corrosion potential is about -112.1mV. The high-temperature oxidation resistance of the composite absorbing material is tested by a thermogravimetric analyzer, and its initial oxidation temperature is 720℃.
[0084] In summary, the composite absorbing material prepared in this embodiment has the characteristics of good absorbing performance, corrosion resistance and high-temperature oxidation resistance, and the powder formation rate of the high-entropy alloy spherical powder in this embodiment is relatively high.
[0085] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent structural transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A dielectric and magnetic loss coupling multi-frequency high absorption composite absorbing material, characterized in that: The chemical formula of the composite absorbing material is (FeCoNiCr a Mn) x ·(BaTiO3) y , the value range of a is 0.1~1, and the ratio of y to x is not greater than 1.
2. The dielectric and magnetic loss coupling multi-frequency high absorption composite absorbing material according to claim 1, characterized in that: The chemical formula of the composite absorbing material is (FeCoNiCr 0.8 Mn)1·(BaTiO3) 0.2 .
3. A method for preparing the dielectric and magnetic loss coupling multi-frequency high absorption composite absorbing material as claimed in claim 1 or 2, characterized in that: The preparation method comprises the following steps: Step 1: Mix metal iron, metal cobalt, metal nickel, metal chromium and metal manganese and perform suspension smelting multiple times to prepare alloy ingots, then perform vacuum gas atomization, and obtain high entropy alloy spherical powder after sieving; Step 2: subjecting the high entropy alloy spherical powder obtained in step 1 to a first ball milling under an argon atmosphere to obtain a lamellar high entropy alloy; a process control agent is added during the first ball milling; Step 3, naturally cooling the flaked high entropy alloy obtained in step 2 and then drying it to obtain a dry flaked high entropy alloy; Step 4: Mix the dried flaky high entropy alloy obtained in step 3 with barium titanate powder, and then perform a second ball milling in an argon atmosphere. After natural cooling, a product having a chemical formula of (FeCoNiCr a Mn) x ·(BaTiO3) y The composite absorbing material; the second ball mill adopts a dry grinding process.
4. The method for preparing a dielectric and magnetic loss coupling multi-frequency high absorption composite absorbing material according to claim 3, characterized in that: The mass purity of the metallic iron, metallic cobalt, metallic nickel, metallic chromium and metallic manganese in step 1 is greater than 99.7%.
5. The method for preparing a dielectric and magnetic loss coupling type multi-frequency high absorption composite absorbing material according to claim 3, characterized in that: The vacuum degree of the suspension smelting in step 1 is not greater than 1×10 -3 After each suspension smelting, the alloy ingot is turned over, and the number of suspension smelting is not less than 5 times; the vacuum degree of the vacuum gas atomization is not greater than 1×10 -3 The temperature of the vacuum air atomization is 1200° C. to 1600° C., the heating power of the vacuum air atomization is 10 kW to 25 kW, and the heating time of the vacuum air atomization is 60 min to 100 min.
6. The method for preparing a dielectric and magnetic loss coupling multi-frequency high absorption composite absorbing material according to claim 3, characterized in that: The sieving time of the sieving in step 1 is 10 minutes to 45 minutes, the particle size of the high entropy alloy spherical powder is not greater than 53 μm, and the mass of the high entropy alloy spherical powder accounts for 40% to 60% of the total mass of the vacuum gas atomization product.
7. The method for preparing a dielectric and magnetic loss coupling multi-frequency high absorption composite absorbing material according to claim 3, characterized in that: The first ball milling process in step 2 is: the high entropy alloy spherical powder and the process control agent are loaded into a stainless steel ball milling jar for vacuum pump evacuation and argon gas washing, and after sealing, the ball milling jar is loaded into a high-energy ball mill for 12h to 24h of ball milling, and the high-energy ball mill is stopped for 5min to 8min after each 30min to 60min of ball milling; the first ball milling speed is 300r / min to 600r / min, the mass ratio of the stainless steel grinding balls to the high entropy alloy spherical powder in the stainless steel ball milling jar is 5 to 20:1, and the diameter size of the stainless steel grinding balls includes one or more of 10mm, 8mm and 6mm.
8. The method for preparing a dielectric and magnetic loss coupling multi-frequency high absorption composite absorbing material according to claim 3, characterized in that: The process control agent in step 2 is one of anhydrous ethanol, stearic acid, acetone, and deionized water, and the added amount of the process control agent is 10 mL to 50 mL.
9. The method for preparing a dielectric and magnetic loss coupling multi-frequency high absorption composite absorbing material according to claim 3, characterized in that: The drying in step 3 is vacuum drying, the drying temperature is 40° C. to 80° C., and the drying time is 8 h to 30 h.
10. The method for preparing a dielectric and magnetic loss coupling multi-frequency high absorption composite absorbing material according to claim 3, characterized in that: In step 4, the second ball milling adopts a high-energy ball mill, the rotation speed of the second ball milling is 300r / min to 600r / min, and the time of the second ball milling is 20min to 60min.
Citation Information
Cited By
Sheet branch type magnetic nano material as well as preparation and application thereof
CN120170069A
Flaky high-entropy alloy material containing refractory metal and preparation method of flaky high-entropy alloy material
CN120989475A